Crystallization of the Na2FexNi1−xP2O7 Glass and Ability of Cathode for Sodium-Ion Batteries - Ji, Yongzheng; Honma, Tsuyoshi; Komatsu, Takayuki (Frontiers in Materials, 2020)
The positive electrode active materials based on the Ni3+/2+ redox reaction are rarely reported due to its poor kinetics exhibited in the sodium phosphate. Here in, we substitute active Fe for a part of Ni, expecting to activate the potential deriving from the Ni3+/2+ in Na2FexNi1-xP2O7 glass-ceramics. Precursor glasses were prepared by melt-quenching method and exhibits surface crystallization tendency due to heterogeneous nucleation. In the charge-discharge testing, all the flat potential exhibited in the discharge process derived from the reduction of Fe3+/2+. However, from the dQ/dV plot, there were two weak reduction peaks at 4.3 V and 4.4 V in the discharge process of Na2Fe0.25Ni0.75P2O7. Combining with the oxidation peak at 4.6 V in the second charge process of Na2NiP2O7, we believe the reduction peaks at 4.3 V and 4.4 V were derived from the Ni3+/2+.